FAKTOR- FAKTOR YANG MEMPENGARUHI TINGKAT PENGUNGKAPAN LAPORAN KEUANGAN PEMERINTAH DAERAH - Sucahyo Heriningsih; Rusherlistyanti . (Jurnal Ekonomi Dan Bisnis, 2015)
This research is aimed to  examine the influence of the characteristics and level of accountability from local government to local government financial statement disclosure. The samples numbered 46 cities andcounties are taken from the BPK, sampling using purposive sampling method and using multiple linearregression analysis. The results of the study shows that the characteristics  of the  local  government  (dependency  rate  and   the size of  the  local  government) and  the  level of accountability  (the  auditor's  opinion, the   weakness  of  the SPI, non-compliance with  the  law)  does  not  affect the local government's financial statement disclosure. Keywords: characteristics of local government, the level of accountability of local government, local government financial statement disclosure.